Corrigendum to: “Oral subchronic exposure to the mycotoxin ochratoxin A induces key pathological features of Parkinson's disease in mice six months after the end of the treatment” [Food Chem. Toxicol. (2021) 152 112164] - María Izco; Ariane Vettorazzi; Raquel Forcen; Javier Blesa; Maria de Toro; Natalia Alvarez-Herrera; J Mark Cooper; Elena Gonzalez-Peñas; Adela Lopez de Cerain; Lydia Alvarez-Erviti (Food and Chemical Toxicology, 2026)

Pig slurry valorization by ammonia recovery, biogas upgrading and microbial protein production - Amanda Prado de Nicolás; Andreu Serra-Toro; Maria Ventura; Sergi Astals; Joan Dosta; Francesc Mas; Yolanda Segura; Juan A. Melero; Fernando Martínez; Daniel Puyol (Bioresource Technology, 2025)

Predictors of Salmonella enterica contamination in agricultural and livestock-impacted natural watersheds - Alan D.L. Rocha; Laiorayne A. Lima; Gustavo F.C. Sales; Nadyra J. Silva; Maria L.R. Gomes; Walter E. Pereira; Patrícia E.N. Givisiez; Eric W. Brown; Marc W. Allard; Rebecca L. Bell; Magaly Toro; Jianghong Meng; et al. (Environmental Pollution, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Analysis of residual feed intake in Nellore bulls of different ages, rib eye area, and backfat thickness - Matheus Henrique Vargas de Oliveira; Jessica Moraes Malheiros; Alejandra Maria Toro Ospina; Pablo Dominguez-Castaño; Lorena Ferreira Benfica; Luiz Eduardo Cruz dos Santos Correia; Leila de Genova Gaya; Maria Eugênia Zerlotti Mercadante; André Michel de Castilhos; Joslaine Noely dos Santos Gonçalves Cyrillo; Jéssica Biasotto Sartori; Lúcia Galvão de Albuquerque; et al. (Tropical Animal Health and Production, 2022)

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Genetic principal components for reproductive and productive traits in Holstein cows reared under tropical conditions - Pablo Dominguez-Castaño; Alejandra Maria Toro Ospina; Lenira El Faro; Josineudson Augusto II de Vasconcelos Silva (Tropical Animal Health and Production, 2021)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Cold-Adapted Digestive Aspartic Protease of the Clawed Lobsters Homarus americanus and Homarus gammarus: Biochemical Characterization - Liliana Rojo; Fernando García-Carreño; Maria de los Angeles Navarrete del Toro (Marine Biotechnology, 2013)